Hubungan Tingkat Penggunaan Gadget dengan Kelelahan Mata Dan Interaksi Sosial Anak pada Siswa di Sekolah Dasar Negeri Cinere 03 - Amelia Kurniawati; Sumedi Sumedi; Sri Mintasih (Lembaga Pengembangan Kinerja Dosen, 2024)
Introduction: Gadgets are electronic devices that are specialized for certain purposes, which are around us such as cellphones, tablets, computers. Among the many gadgets available, children spend their time playing with cellphones, tablets, or excessive use of gadgets can cause eye health problems such as eye fatigue and social interaction. Objective: To determine the relationship between the level of excessive gadget use and eye fatigue and changes in children's social interactions among students at Cinere 03 State Elementary School. Method: This research is a quantitative study with a cross sectional design on a sample of 97 students with total sampling using the Spearman rank correlation analysis test. Results: The research results showed that the majority of respondents were female, 50 students (51.5%), the majority of respondents were 12 years old, 48 students (49.5%), the level of gadget use in the medium category was 63 students (64.9%) , 49 students (50.5%) experienced eye fatigue in the no category, 73 students (75.3%) experienced social interaction in the sufficient category. The results of the analysis using Spearman rank correlation in the first hypothesis obtained a value of 0.295 (p>0.05), and the second hypothesis obtained a value of 0.939 (p>0.05). Suggestion: For children who are at risk of eye fatigue symptoms, this can be done by using the technique of working in front of a gadget or computer for 20 minutes, then looking at an object about 20 feet or meters away for 20 seconds and looking away from the screen.